Toward Sustainable Construction Using Wood Material: A Review of Indicator-based Sustainability Assessments - Lestari, Lestari; Ikaputra, Ikaputra (International Journal of Environment, Architecture, and Societies, 2024)
The largest consumer of resources and contributor to CO2 emissions is the industrial sector. Sustainable construction is an approach that addresses these issues. As a significant factor influencing energy consumption and emissions in the construction industry, there is a notable shift in the use of building materials towards those derived from natural sources. Wood, which has renewable properties and is a CO2 sink, is an alternative material to consider. The objective of this paper is to provide a critical analysis of the utilization of wood as a material in the context of sustainable construction. The paper is structured by a review of the relevant literature on the subject, obtained from various academic database sources. The paper outlines the meaning of sustainability and sustainable construction and reviews wood materials in supporting sustainable construction through existing indicators. The results show the important role of wood in supporting sustainable construction from social, economic, environmental, and technological aspects. Some disadvantages of wood materials are the focus of some literature by providing alternative solutions through technology, responsible management, and policy.